Treatment of Vulvar Angiolymphoid Hyperplasia with Eosinophilia with Topical Corticosteroids - Nor Fazil Jaber; Britta Krynitz; Philip Curman (Medical Journals Sweden, 2023)
Abstract is missing (Short communication)